Sir Cumference speaks volumes - Neuschwander, Cindy (Sir Cumference math adventure series, 2024)
"Sir Cumference and Lady Di learn a method to calculate the volume of grain needed to feed everyone at the castle during a blizzard"-- Provided by publisher.